Atlantic salmon, Salmo salar L. are broadly susceptible to isolates representing the North American genogroups of infectious hematopoietic necrosis virus - Kurath, G (Journal of fish diseases, 2016)
Published 2014. This article is a U.S. Government work and is in the public domain in the USA.